Optimal sleep duration in the subarctic with respect to obesity risk is 8-9 hours - Johnsen, May Trude; Wynn, Rolf; Bratlid, Trond (PLoS ONE, 2013)
Sleep duration, chronotype and social jetlag have been associated with body mass index (BMI) and abdominal obesity. The optimal sleep duration regarding BMI has previously been found to be 7–8 hours, but these studies have not been carried out in the subarctic or have lacked some central variables. The aims of our study were to examine the associations between sleep variables and body composition for people living in the subarctic, taking a range of variables into consideration, including lifestyle variables, health variables and biological factors. The cross sectional population Tromsø Study was conducted in northern Norway, above the Arctic Circle. 6413 persons aged 30–65 years completed questionnaires including self-reported sleep times, lifestyle and health. They also measured height, weight, waist and hip circumference, and biological factors (non-fasting serum level of cholesterol, HDLcholesterol, LDL-cholesterol, triglycerides and glucose). The study period was from 1 October 2007 to 19 December 2008. The optimal sleep length regarding BMI and waist circumference was found to be 8–9 hours. Short sleepers (,6 h) had about 80% increased risk of being in the BMI$25 kg/m2 group and male short sleepers had doubled risk of having waist circumference $102 cm compared to 8–9 hours sleepers. We found no impact of chronotype or social jetlag on BMI or abdominal obesity after controlling for health, lifestyle, and biological parameters. In our subarctic population, the optimal sleep duration time regarding risk of overweight and abdominal obesity was 8–9 hours, which is one hour longer compared to findings from other studies. Short sleepers had 80% increased risk of being overweight, and men had a doubled risk of having abdominal obesity. We found no associations between chronotype or social jetlag and BMI or abdominal obesity, when we took a range of life-style, health and biological variables into consideration.